2021
DOI: 10.1021/acs.jpcc.1c01918
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Vacancy and Ti Doping in 2D Janus MoSSe on Photocatalysis

Abstract: Two-dimensional (2D) Janus transitional metal dichalcogenides (TMDCs) have great potential for photocatalytic water splitting due to their novel properties induced by the unique out-of-plane asymmetric structures. Here, we systematically investigate the geometric, electronic and optical properties of 2D Janus MoSSe with titanium doping and vacancies to explore their synergistic effects on photocatalytic activity. We find that there are effective attractions between the substituted or adsorbed Ti atoms and S/Se… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 61 publications
0
16
0
Order By: Relevance
“…However, the visible light utilization efficiency of the Janus WSSiN 2 monolayer is still far from satisfactory. Recently, it has been confirmed that some additional strategies, such as doping, heterojunction coupling, and strain engineering, could be employed to improve optical absorption and enhance the energy conversion efficiency of 2D materials. , For example, Kou et al found that the optical absorption of Janus WSSe monolayer can be effectively broadened under the small tensile strains of 1%. Thus, it is expected to boost the optical properties using similar methods in future work.…”
Section: Resultsmentioning
confidence: 99%
“…However, the visible light utilization efficiency of the Janus WSSiN 2 monolayer is still far from satisfactory. Recently, it has been confirmed that some additional strategies, such as doping, heterojunction coupling, and strain engineering, could be employed to improve optical absorption and enhance the energy conversion efficiency of 2D materials. , For example, Kou et al found that the optical absorption of Janus WSSe monolayer can be effectively broadened under the small tensile strains of 1%. Thus, it is expected to boost the optical properties using similar methods in future work.…”
Section: Resultsmentioning
confidence: 99%
“…59 Furthermore, excellent photocatalysts for water splitting to produce hydrogen have been widely studied. [60][61][62][63] Until now, many 2D materials have been theoretically predicted and experimentally identified to be the promising optical and photocatalytic materials. Excellent photocatalysts for water splitting should satisfy several important features.…”
Section: Optical and Photocatalytic Propertiesmentioning
confidence: 99%
“…Consequently, the photocatalytic decomposition of water using sunlight to produce hydrogen has garnered significant attention. 20,[62][63][64] To achieve efficient photocatalytic water decomposition, several crucial characteristics must be met. Catalysis Science & Technology Paper and these can participate in hydrogen and oxygen generation through the following reactions: 2H + + 2e − → H 2 and 2H 2 O + 4h + → 4H + + O 2 .…”
Section: Band Alignmentmentioning
confidence: 99%